Електронна структура 3R-полiтипiв диселенiдiв нiобiю та молiбдену - Синельниченко, О.К.; Тишковець, Ж. I.; Карпець, М.В.; Хижун, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
X-ray photoelectron spectroscopy (XPS) is used to investigate the electronic structure of 3R−Nb1.14Se2 and 3R−MoSe2 compounds. For the mentioned compounds, the XPS valence-band and Nb(Mo)3d and Se3p core-level spectra are derived. For comparison, the similar spectra are obtained for the usual 2H polymorphous forms of niobium and molybdenum diselenides, 2H(a)−NbSe2 and 2H(c)−MoSe2, respectively. The half-width of the XPS valence-band spectrum decreases when going from niobium diselenides to molybdenum diselenides under consideration. The charge transfer occurring in the direction from the metal atoms to selenium atoms decreases in the above sequence of compounds.